Dual apprenticeship training of refugees: potential for integration and securing skilled labour? The importance of companies’ recruiting problems and digitalisation - Weis, Kathrin [Verfasser] (My University, 2024)
„Dual apprenticeship training is discussed as a promising strategy for the labour market integration of refugees. In this process, companies play a central role. In dependence of their regional and occupational situation, they themselves are faced with the problem of not finding apprentices for the training places they offer. Are companies with vacant VET positions more likely to train refugees than companies without vacant VET positions? And in which relationship does the apprenticeship training of refugees stay with the technological infrastructure of the company? Multivariate panel analysis of the BIBB-Establishment Panel on Training and Competence Development 2016 & 2017 expand the empirical evidence, existing up to 2018: The higher probability of VET-contracts between refugees and companies with vacant VET-positions than with companies without vacant VET-positions, suggests that companies, on the one side, recognize the potential of the additional group of applicants to fill hard-to-fill apprenticeship training places, and refugees, on the other side, take advantage of the higher chances of access to companies struggling to find apprentices. Regarding the technological infrastructure the analysis shows that it depends on the specific technologies, whether they foster or hinder the apprenticeship training of refugees. The article is based on the situation in Germany in the years 2015–2017. Results cannot be easily transferred to other periods (or countries), as the integration capacity of the dual apprenticeship training system depends heavily on factors such as the socio-economic characteristics of the immigrants considered at the time.“ (author’s abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; S 3.2 Unternehmen und Behörden; 370; Flüchtling; Berufsausbildung; Ausbildungschance; Betrieb; Ausbildungsverhalten; Unbesetzte Ausbildungsplätze; Digitalisierung